STRATEGI PENGEMBANGAN SARANA DAN PRASARANA AGROWISATA BALE ANGGUR DI KAWASAN DESA BATUJAI KECAMATAN PRAYA BARAT KABUPATEN LOMBOK TENGAH - Anwar, Ihza Izaldi; Sulistiyono, Heri; Salmah, Emi (Universitas Mataram, 2024)
Batujai Village is a village located in Central Lombok Regency, West Nusa Tenggara Province, Indonesia. This village is known for its beautiful natural scenery and agricultural potential. Apart from that, Batujai is also often an attractive tourist location for visitors who want to enjoy the rural atmosphere of Lombok. Therefore, the aim of the KKN PMD at Mataram University is to see potential so that it tries to realize development strategies for facilities and infrastructure that have not been optimally implemented by the local community. The implementation method used in this research uses SWOT analysis where researchers together with the KKN team analyze the strengths, weaknesses, opportunities and obstacles that occur in this grape bale area. The results obtained are the creation of better facilities and infrastructure for the area, coupled with the development and creation of works that add to the aesthetics of the area, it is hoped that this will attract more tourists who visit the winery.